TeraHertz laser generation by optically pumped polar molecules - Costa, L. F.L.; Viscovini, R. C.; Morais, J. C.S. [UNESP]; Cruz, F. C.; Pereira, D. (Optica Publishing Group, 2007)
In this work we report 12 new optically pumped far-infrared (FIR) laser lines from CH3OH and 19 from 13CH3OH. A 13CO2 laser of wide tunability (110 MHz) was used as pump source, and a Fabry-Perot open cavity was used as a FIR laser resonator. © 2007 Optical Society of America.